Transgenerational Colonial Trauma and Disordered Eating in the Work of Maaza Mengiste and Igiaba Scego - Kane, Noreen (Quaderni d'Italianistica, 2023)
This essay analyzes how Ethiopian American Maaza Mengiste’s novel Beneath the Lion’s Gaze (2010) and Somali Italian Igiaba Scego’s memoir La mia casa è dove sono (My Home Is Where I Am, 2010) represent transgenerational colonial trauma through their female protagonists’ relationships to food. Employing Nicholas Abraham and Maria Torok’s theory of transgenerational haunting, the corporeal transmission of Italian colonial trauma is explored. To supplement classic trauma theory, the work of Afrofeminist scholars who posit the importance of intersubjectivity in approaches to trauma is employed. The essay thus explores how these two literary texts render the legacy of colonial violence visceral through an emphasis on the body, the process of transforming somatic symptoms into narrative, and the necessity of community building to working through generational trauma. In their contribution to the formation of a transnational collective memory of Italian colonialism in Ethiopia and Somalia, the texts invite the reader to consider their position in relation to this trauma.